Investigation of vegetable and fruit intake of First Nation schoolchildren: Do school nutrition programs make a difference? - Gates, Allison (University of Waterloo, 2010)
Objectives: To investigate the vegetable and fruit, “other” foods, fibre, folate, vitamin A, and vitamin C intakes of First Nations children and adolescents residing in seven communities in northern and southern Ontario, including variations by year and community, and comparisons to current dietary standards and national averages based on age and sex. Also, to implement and assess the impact of two school nutrition programs (in Kashechewan and Fort Albany, Ontario) on dietary intakes of vegetable and fruit, “other” foods, fibre, folate, vitamin A, and vitamin C. Also, to evaluate the two school nutrition programs, one a simple food provision program in Kashechewan, Ontario and the other a more comprehensive school nutrition program in Fort Albany, Ontario, in terms of student and teacher impressions and program integrity. For the program in Fort Albany, the impact of the program on nutrition knowledge, self-efficacy, and intentions to eat more vegetables and fruit will also be assessed. Finally, to investigate the association between Body Mass Index (BMI) and vegetable and fruit and fibre intake in First Nations children and adolescents living on reserve in Ontario. Methods: Dietary intakes were evaluated using 24-hour dietary recall data collected via the validated Web-Based Eating Behaviour Questionnaire (WEB-Q) between 2003 and 2010 in seven First Nations communities in northern (Attawapiskat, Fort Albany, Kashechewan, Moose Factory, and Peawanuck) and southern (Christian Island and Georgina Island) Ontario. Vegetable and fruit, “other” foods, fibre, folate, vitamin A, and vitamin C intakes were compared to current dietary standards and Canadian Community Health Survey Cycle 2.2 (CCHS). Yearly and community differences in intakes were assessed using specific dataset pairs to control for season, year, and community, where conditions were comparable. The association between vegetable and fruit and fibre intake and BMI was investigated using the weight classifications described by Cole and colleagues (2000) and ...